Complex dynamic behaviors in a new Colpitts oscillator topology based on a voltage comparator - Kountchou, M. (2020)
Designing simple chaotic circuits with complex dynamic behaviors that can generate coexisting and hidden attractors has attracted much interest recently. In this paper, a new voltage-tunable Colpitts oscillator based on a two op-amps voltage comparator that can exhibit self-excited and hidden behaviors is proposed. Only the intrinsic nonlinearity of the voltage comparators is responsible for the complex dynamic behaviors of the proposed model and no additionally nonlinear devices are required. In this circuit, a reference voltage source acts as a reversible control parameter, since it can be varied indifferently in a positive or negative direction. Basic dynamic properties of the proposed Colpitts oscillator are investigated and the entire dynamics is analyzed numerically based on standard nonlinear analytical tools. Very rich dynamic behaviors and phenomena are reported, including; hidden attractors, period-doubling bifurcations, antimonotonicity, bursting oscillations, offset-boosting, and coexistence of multiple attractors for a set parameter values of the system. PSpice simulations are also carried out to validate theoretical and numerical results. Furthermore, the feasibility of the proposed Colpitts oscillator is confirmed through a practical realization which is in good agreement with the theoretical results.